Zum Begriff "Kompetenz" in der Fremdsprachendidaktik - Czarnecka, Małgorzata (Glottodidactica, 2008)
This paper discusses the role of the notion of competence in foreign language teaching. The starting point is a definition of competence given by Chomsky and other researchers over a span of several decades (Labov, Hymes, Canale & Swain, Coseriu, tyons et al.). In the latter part of the paper, a model of communicative competence by Hans Eberhard Piepho is presented. The author focuses on changes the notion of competence has undergone within the period under consideration; they are presented as a process that - in the linguistics - has manifested itself for years in a tendency „towards the performance".